Additional features in Brugada Syndrome stratification: frequent PVC and QRS duration. (19th May 2022) - Couto Pereira, S; Brito, J; Silverio Antonio, P; Velente Silva, B; Alves Da Silva, P; Simoes De Oliveira, C; Garcia, B; Lima Da Silva, G; Carpinteiro, L; Cortez-Dias, N; Pinto, FJ; De Sousa, J
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Brugada syndrome (BrS) is a channelopathy with high prevalence of malignant arrhythmic events. The risk stratification in patients (pts) with Brugada electrocardiographic (ECG) pattern is of major importance, to prevent sudden cardiac death (SCD). A higher risk is evidenced in spontaneous type 1 pattern when compared with induced type-1 pattern, as so other electrocardiographic features have been explored aiming to detect additional prognostic factors. Purpose: To evaluate the association of QRS duration and frequent premature ventricular contractions (PVC) with malignant arrhythmic events. Methods: Prospective single-center study of consecutive pts with BrS, with spontaneous or induced type 1 pattern included from 2003 to 2021. All pts were enrolled in a protocol including annual non-invasive assessment with ECG and 24-hours Holter monitoring. Primary endpoints were defined as SCD or appropriate shocks in the context of ventricular tachycardia or fibrillation (VT/FV) during follow-up. Cox regression and Kaplan-Meier survival analyses were used to determine the association between the baseline ECG and Holter characteristics and the long-term risk of arrhythmic events. Results: A total of 117 pts was included, 75 (65%) with a spontaneous type 1 pattern and 44 (33%) with an induced type 1 pattern. The mean age was 47±13years and 38 (32.5%) were male. During a median follow-up of 4.1±0.3 years, the primary endpoint occurred in 8 (6.8%) pts, with sudden cardiac death in 3 (2.6%) and appropriate shocks due to VT/FV in 5 (4.3%). Pts who suffered arrhythmic events had presented at the study inclusion higher QRS duration (124±18 vs. 108±16ms, p= 0.014) and more frequent PVCs on 24-hour Holter (169±297 vs. 29±198; p = 0.001) - Figure 1. Indeed, the presence of QRS ≥119ms was associated with a 7-fold higher risk (HR: 7.250, 95% CI 1.619-32.461, p = 0.010) and the presence of more than 6 PVC on 24-hour Holter was also associated with a 5-fold higher risk of malignant arrhythmic events (HR 5.376, 95% 1.186-24.260, p = 0.029). Conclusion: QRS duration and frequent PVC may established themselves as additional risk factors. In our cohort, they were both predictors of arrhythmic events during follow-up and thus can further complement BrS risk stratification.